Shifted Dynamics of Glucose Metabolism in the Hippocampus During Aging - Ge, Ivan; Kirschen, Gregory Wohl; Wang, Xinxing (Frontiers in Aging Neuroscience, 2021)
Aging is a process that adversely affects brain functions such as cognitive behaviors. Brain activity is a high-energy consumption process. Glucose serves as the main energy source under normal circumstances. Whether the dynamics of glucose metabolism during aging remains unchanged is not well understood. This study sought to investigate the activity-dependent changes in glucose metabolism of the mouse hippocampus during aging. In brief, after one hour of contextual exploration in an enriched environmental condition or one hour in a familiar home cage condition, metabolites were measured from the hippocampus of both young adult and aged mice with metabolomic profiling. Compared to the home cage context, the enriched contextual exploration condition resulted in changes in the concentration of 11 glucose metabolism-related metabolites in the young adult hippocampus. In contrast, glucose metabolism-related metabolite changes were more apparent in the aged group altered by contextual exploration when compared to those in the home cage condition. Importantly, in the aged groups, several key metabolites involved in glycolysis, the TCA cycle, and ketone body metabolism accumulated, suggesting the less efficient metabolization of glucose-based energy resources. Altogether, the analyses revealed that in the aged mice altered by enriched contextual exploration, the glucose resource seems to be unable to provide enough energy for hippocampal function.